2009
DOI: 10.1124/dmd.109.027003
|View full text |Cite
|
Sign up to set email alerts
|

Substrate-Dependent Functional Alterations of Seven CYP2C9 Variants Found in Japanese Subjects

Abstract: ABSTRACT:CYP2C9 is a polymorphic enzyme that metabolizes a number of clinically important drugs. In this study, catalytic activities of seven alleles found in Japanese individuals, CYP2C9*3 (I359L), *13 (L90P), *26 (T130R), *28 (Q214L), *30 (A477T), *33 (R132Q), and *34 (R335Q), were assessed using three substrates (diclofenac, losartan, and glimepiride). When expressed in a baculovirus-insect cell system, the holo and total (apo and holo) CYP2C9 protein expression levels were similar among the wild type (CYP2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
54
2
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 56 publications
(64 citation statements)
references
References 33 publications
(51 reference statements)
7
54
2
1
Order By: Relevance
“…1 and Table 1, the typical variant CYP2C9.3 exhibited approximately 8.6%-38.9% of the enzymatic activity of wild-type CYP2C9.1 toward tolbutamide, diclofenac, and losartan. When expressed in insect cell microsomes, previous reports revealed that typically defective variant CYP2C9.3 exhibited higher K m and/or decreased V max values than the wild-type enzyme for the hydroxylation of probe drugs diclofenac and losartan (Dickmann et al, 2001;Maekawa et al, 2009). Our data were quite consistent with those observed in previous studies.…”
Section: Downloaded Fromsupporting
confidence: 83%
“…1 and Table 1, the typical variant CYP2C9.3 exhibited approximately 8.6%-38.9% of the enzymatic activity of wild-type CYP2C9.1 toward tolbutamide, diclofenac, and losartan. When expressed in insect cell microsomes, previous reports revealed that typically defective variant CYP2C9.3 exhibited higher K m and/or decreased V max values than the wild-type enzyme for the hydroxylation of probe drugs diclofenac and losartan (Dickmann et al, 2001;Maekawa et al, 2009). Our data were quite consistent with those observed in previous studies.…”
Section: Downloaded Fromsupporting
confidence: 83%
“…b Dose adjustment ratios were predicted at the upper most value of estimated f m(CYP2C9) . dmd.aspetjournals.org features of CYP2C9 [i.e., a big active pocket allowing simultaneous binding of multiple ligands (Williams et al, 2003)] that potentially lead to highly substrate-dependent functionality of CYP2C9 variants (Maekawa et al, 2009). It will be of interest to examine whether the partition ratios, metabolite formation rates, and noscapine depletion rates are significantly different among these enzymes.…”
Section: Discussionmentioning
confidence: 99%
“…Combined with the functional analysis data, our present data suggested that CYP2C9*16 was another important defective CYP2C9 allele for Chinese Han individuals, except for the commonly studied alleles *2, *3, and *13. Maekawa et al (2009) reported that recombinant microsome of CYP2C9*34 had no substantial effect on the metabolism of diclofenac, losartan, and glimepiride. However, in the present study, CYP2C9*34 exhibited decreased catalytic activity for tolbutamide in COS-7 cells, which is consistent with activity in vivo.…”
Section: Discussionmentioning
confidence: 99%
“…When expressed in a baculovirus-insect cell system, CYP2C9*34 had no substantial effect. A study on substratedependent functional alteration of CYP2C9 demonstrated that CYP2C9*34 exhibited catalytic activities almost similar to those of the wild-type for diclofenac, losartan, and glimepiride (Maekawa et al, 2009). …”
Section: Introductionmentioning
confidence: 99%